Ethnicity‐related variations of left ventricular remodeling in adolescent amateur football players. Issue 3 (27th April 2014) - Pelà, G.; Li Calzi, M.; Crocamo, A.; Pattoneri, P.; Goldoni, M.; Anedda, A.; Musiari, L.; Biggi, A.; Bonetti, A.; Montanari, A.
<x xml:space="preserve">Abstract</x> Adult and adolescent elite black athletes display – as compared with their white counterparts – excessively increased left ventricle (LV) wall thickness (LVWT), mass (LVM), and relative wall thickness (RWT). To investigate such ethnicity‐related differences in non‐professional adolescent athletes, 138 male, amateur football players [age 14.0 ± 1.7 years, 42 West‐African blacks (BA) and 96 Italian whites (WA)] underwent an echocardiographic study of LV diameters, LVWT, maximal wall thickness (MWT), LVM, and RWT as remodeling index. BA vs WA exhibited greater thickness of septum and posterior wall, higher MWT (10.3 ± 1.7 vs 8.8 ± 1.1 mm), and higher LVM (117 ± 27 vs 101 ± 20 g/m2) and RWT (0.44 ± 0.07 vs 0.35 ± 0.04). Age, systolic blood pressure, body mass index, and ethnicity predicted MWT and LVM, whereas ethnicity was the sole strong predictor of RWT. The greater MWT, LVWT, and LVM of 14‐year‐old, amateur‐level BA vs WA indicates that ethnicity substantially affects LV structure in adolescent, non‐professional athletes. In contrast with MWT and LVM, elevated RWT was predicted by black ethnicity only. We suggest that concentric‐type LV remodeling is a peculiar LV phenotype in adolescent African athletes.